2016
DOI: 10.1021/jacs.5b11341
|View full text |Cite|
|
Sign up to set email alerts
|

Anisotropic Growth of TiO2 onto Gold Nanorods for Plasmon-Enhanced Hydrogen Production from Water Reduction

Abstract: Plasmonic metal/semiconductor heterostructures show promise for visible-light-driven photocatalysis. Gold nanorods (AuNRs) semi-coated with TiO2 are expected to be ideally structured systems for hydrogen evolution. Synthesizing such structures by wet-chemistry methods, however, has proved challenging. Here we report the bottom-up synthesis of AuNR/TiO2 nanodumbbells (NDs) with spatially separated Au/TiO2 regions, whose structures are governed by the NRs' diameter, and the higher curvature and lower density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
434
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(441 citation statements)
references
References 46 publications
7
434
0
Order By: Relevance
“…[56] As shown in Figure 6, the as-synthesized AuNR-TiO 2 photocatalyst showed a spatially separated dumbbell structure (Figure 6a-h …”
Section: Effects Of Metal-semiconductor Configurationmentioning
confidence: 91%
“…[56] As shown in Figure 6, the as-synthesized AuNR-TiO 2 photocatalyst showed a spatially separated dumbbell structure (Figure 6a-h …”
Section: Effects Of Metal-semiconductor Configurationmentioning
confidence: 91%
“…Previous studies have demonstrated that the LSPR property of bimetallic core-shell nanostructures can significantly facilitate their catalytic activity for many important reactions, such as hydrogen production from water splitting, 14,15,54 dehydrogenation of formic Bimetallic AuRh nanodendrites Y Kang et al acid 17 and a Suzuki coupling reaction. 55 The unique heterostructure and LSPR optical property of bimetallic Au@Rh core-shell nanodendrites offer the possibility of light-enhanced catalytic applications.…”
Section: Light-enhanced Catalytic Activity For the Hgr-n 2 Hmentioning
confidence: 99%
“…12,13 Among various bimetallic nanostructures, Au-based core-shell-type noble metal nanostructures have been widely employed in various important heterogeneous catalytic reactions, especially in lightenhanced catalytic reactions, originating from the high mass activity of noble metal shells and the distinctive localized surface plasmon resonance (LSPR) of Au nanocrystal cores. [14][15][16][17] In most bimetallic core-shell nanodendrites, the metal shells consist of spherical nanocrystals. 5,18,19 Recently, the atomically thick noble metal nanoplates, an emerging star nanomaterial for the catalysis, have attracted more attention compared with the traditional zerodimensional noble metal nanocrystals, owing to the extremely high meal atom utilization and superior catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor photocatalysis as a type of green technology for solar energy conversion has exhibited fascinating application prospects in environmental and energy‐relevant areas, such as photocatalytic degradation of pollutants and photocatalytic hydrogen generation 1. In the wave of photocatalysis research, graphitic carbon nitride (g‐C 3 N 4 )‐based photocatalysts have been significantly flourishing2 since its promising utilization for water splitting under visible‐light irradiation reported in 2009 3.…”
mentioning
confidence: 99%